The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/10738584221082620
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting Astrocyte Diversity through Circuits and Transcription

Abstract: Astrocytes are the most abundant glial cell in the central nervous system and occupy a wide range of roles that are essential for brain function. Over the past few years, evidence has emerged that astrocytes exhibit cellular and molecular heterogeneity, raising the possibility that subsets of astrocytes are functionally distinct and that transcriptional mechanisms are involved in encoding this prospective diversity. In this review, we focus on three emerging areas of astrocyte biology: region-specific circuit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Neuronal activity-dependent astrocyte transcriptional and epigenomic changes control olfactory processing. Neuronal activity induces widespread transcriptional changes in astrocytes (1), which is exemplified by Sox9 DNA-binding changes after odor-evoked neuronal activation (2). Slc22a3 (3) represents a Sox9-regulated and activitydependent olfactory bulb target that controls astrocytic serotonin (5HT) levels to coordinate histone serotonylation (4), a previously uncharacterized epigenomic mediator of astrocytic GABA release that ultimately affects olfactory processing (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuronal activity-dependent astrocyte transcriptional and epigenomic changes control olfactory processing. Neuronal activity induces widespread transcriptional changes in astrocytes (1), which is exemplified by Sox9 DNA-binding changes after odor-evoked neuronal activation (2). Slc22a3 (3) represents a Sox9-regulated and activitydependent olfactory bulb target that controls astrocytic serotonin (5HT) levels to coordinate histone serotonylation (4), a previously uncharacterized epigenomic mediator of astrocytic GABA release that ultimately affects olfactory processing (5).…”
Section: Resultsmentioning
confidence: 99%
“…◥ NEUROSCIENCE Induction of astrocytic Slc22a3 regulates sensory processing through histone serotonylation Debosmita Sardar 1,2 , Yi-Ting Cheng 1,2,3 †, Junsung Woo 1,2 †, Dong-Joo Choi 1,2 , Zhung-Fu Lee 1,2,4 , Wookbong Kwon 1,2 , Hsiao-Chi Chen 1,2,5 , Brittney Lozzi 1,2,6 , Alexis Cervantes 1,2 , Kavitha Rajendran 1,2 , Teng-Wei Huang 1 , Antrix Jain 7 , Benjamin R. Arenkiel 3,8,9 , Ian Maze 10,11,12 , Benjamin Deneen 1,2,3,4,13 * Neuronal activity drives alterations in gene expression within neurons, yet how it directs transcriptional and epigenomic changes in neighboring astrocytes in functioning circuits is unknown. We found that neuronal activity induces widespread transcriptional up-regulation and down-regulation in astrocytes, highlighted by the identification of Slc22a3 as an activity-inducible astrocyte gene that encodes neuromodulator transporter Slc22a3 and regulates sensory processing in the mouse olfactory bulb.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…neurotransmitters and signaling peptides. 9 This review aims to summarize recent findings regarding the roles of protoplasmic and fibrous astrocytes at the synapse and in the white matter, respectively, with particular attention to their roles in neurodevelopmental and neuropsychiatric disorders.…”
Section: (A) (B)mentioning
confidence: 99%
“…Astrocytes are intimately associated with neuronal activity and neurotransmission, participating in a host of essential roles that facilitate synaptic function (1)(2)(3)(4)(5). A series of prior studies have shown that cell intrinsic activation of Gq-or Gi-signaling and associated Ca 2+ activity in astrocytes can influence a multitude of behavioral outputs, providing key evidence for astrocytic modulation of circuit function (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%